2016
DOI: 10.1093/mnras/stw1497
|View full text |Cite
|
Sign up to set email alerts
|

NoSOCS in SDSS – V. Red disc and blue bulge galaxies across different environments

Abstract: We investigated the typical environment and physical properties of "red discs" and "blue bulges", comparing those to the "normal" objects in the blue cloud and red sequence. Our sample is composed of cluster members and field galaxies at z ≤ 0.1, so that we can assess the impact of the local and global environment. We find that disc galaxies display a strong dependence on environment, becoming redder for higher densities. This effect is more pronounced for objects within the virial radius, being also strong re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 72 publications
5
20
0
Order By: Relevance
“…The disks span the color-mass diagram, but there is no bimodality to suggest a rapid transition through the green valley. This is in agreement with other recent studies of the star formation histories of low redshift disk galaxies (Wolf et al 2009;Masters et al 2010;Tojeiro et al 2013;Lopes et al 2016). …”
Section: Color-mass and Morphologysupporting
confidence: 93%
See 2 more Smart Citations
“…The disks span the color-mass diagram, but there is no bimodality to suggest a rapid transition through the green valley. This is in agreement with other recent studies of the star formation histories of low redshift disk galaxies (Wolf et al 2009;Masters et al 2010;Tojeiro et al 2013;Lopes et al 2016). …”
Section: Color-mass and Morphologysupporting
confidence: 93%
“…We found that is indeed the case, shown by Figure 8. The offset of asymmetry between the blue elliptical peak and the red elliptical peak is evidence that there is at least a significant fraction of blue ellipticals that are associated with mergers, agreeing with recent findings (Smethurst et al 2015;Lopes et al 2016). By visual inspection, it was clear that the galaxies with A > 0.15 were significantly asymmetric.…”
Section: U-r (Dust Corrected)supporting
confidence: 89%
See 1 more Smart Citation
“…Discrepancies among different studies are generally explained by the use of different samples (in terms of luminosity and mass, and wavelength selection), and environment definitions. Regarding the use of AGN selected in different wavelengths the environmental dependence and triggering mechanism for AGN selected in the radio may be different from optical and mid-IR selected AGN (Satyapal et al 2014;Ellison et al 2015), as well as X-rays (Martini et al 2013;Goulding et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…They neither find any evidence suggesting inside-out growth scenario which could turn BSphs to large disks, nor do they see any disk growth around BSphs (but see Graham, Dullo, & Savorgnan 2015;Graham, Ciambur, & Savorgnan 2016;Graham et al 2017, for an alternative view). Lopes et al (2016) also investigated a sample of low-z galaxies in various environments. Their analysis suggests that while highly-asymmetric BSphs may originate in mergers, the star formation histories of BSphs are likely to be heterogenous.…”
Section: Introductionmentioning
confidence: 99%